Nondestructively decorating surface textured silicon with nanorod arrays for enhancing light harvesting. Issue 12 (20th November 2013) - Dong, Wenjing; Huang, Chanyan; Wei, Tiaoxing; Zhang, Yun; Zhang, Kenan; Sun, Yan; Chen, Xin; Dai, Ning
<x xml:space="preserve">Abstract</x> We demonstrate a textured surface antireflection layer containing ZnO nanorod arrays (ZNAs) for light harvesting in a broad wavelength range by a nondestructive and direct procedure based on atomic‐layer deposition and solution growth. The size and morphology of nanorod arrays can be designed according to the textured morphology. The requirements of ZNAs for mc‐Si and c‐Si cells are discussed in detail by controlling their growth conditions, while atomic‐layer deposition is also used for accurate adjustment. By the decoration of nanorod arrays, the weighted average reflectance Rw decreased by more than 56%, resulting in an enhancement of external quantum efficiency and an improvement of about 3.64% for short‐circuit current density. The antireflection method will open up alternative opportunities for achieving feasible, compatible, and nondestructive nonreflecting layers towards optimal light harvesting for PV cells.